Hubunghan Antara Prestasi Belajar dengan Keikutsertaan dan Tingkat Keaktifan dalam Berorganisasi Mahasiswa tahun Kedua dan Ketiga Fakultas Kedokteran Universitas Islam Malang - Anisa, Rizki (Jurnal Kesehatan Islam : Islamic Health Journal, 2018)
ABSTRACT Background : Competence in the field of medical education has been established in SKDI. Non-formal activities (extracurricular) can be used as one of the supporters to achieve competence for example by following the organization. But often this is considered to affect learning achievement. This study aims to determine the relationship between learning achievement with participation and level of student activity in organization in second and third year students of Faculty Of Medicine Islamic University Of Malang.Method : This research is a quantitative research with descriptive analytic design with cross sectional approach and using non parametric statistic test. We used organization activity questionnaire to measure the level of activity in organization.Results : Respondents were 102 students of second and third grade of FK UNISMA. 30 respondents did not follow the organization and 72 followed the organization. The result of data analysis of the relationship between learning achievement and organizational participation was found significance value 0.039 (p <0.05). While the result of data analysis of the relationship between learning achievement and organizational activity level obtained significance value 0.110 (p <0.05).Conclusion : It can be concluded that there is a relationship between learning achievement with the participation of students in the organization but there is no relationship between learning achievement with the level of student activity in the organization. Keywords : student achievement, level of student activity, organization